Co-Relation Of Hba1c Level With Severity Of Diabetic Retinopathy: A Cross-Sectional Study In Ghazipur, UP (The Review of Diabetic Studies, 2025)
Introduction- Diabetes mellitus is a major public health problem in India, with diabetic retinopathy (DR) being a leading cause of preventable blindness. Poor glycaemic control, reflected by elevated HbA1c levels, is strongly linked to DR development and progression. This study evaluates the association between HbA1c levels and DR severity in a regional Indian populationMaterial and Method- This hospital-based cross-sectional study was conducted over 12 months at a tertiary care centre in Ghazipur, Uttar Pradesh. A total of 250 adults with type 2 diabetes mellitus (≥5-year duration) were enrolled. Diabetic retinopathy was graded using standard clinical criteria, and HbA1c levels were estimated by HPLC to assess correlation with retinopathy severity.Result- Diabetic retinopathy was present in 102 patients (40.8%). Among these, mild NPDR was the most common (33.3%), followed by moderate NPDR (29.4%), severe or very severe NPDR (19.6%), PDR without high-risk criteria (9.8%), and PDR with high-risk criteria (7.8%). Mean HbA1c levels increased progressively with DR severity, from 6.8 ± 0.7% in patients without DR to 10.1 ± 1.2% in high-risk PDR. Pearson correlation revealed a strong positive correlation between HbA1c and DR severity (r = 0.66, p < 0.001). Systemic risk factors significantly associated with DR included longer duration of diabetes (≥10 years), poor glycaemic control (HbA1c >8%), hypertension, dyslipidaemia, and insulin therapy. Smoking was not significantly associated with DR.Conclusion- Poor glycaemic control is strongly associated with increasing severity of diabetic retinopathy. Longer diabetes duration, hypertension, dyslipidaemia, and insulin therapy further contribute to DR risk. Early screening, stringent glycaemic control, and comprehensive management of systemic risk factors are crucial to prevent vision-threatening complications, especially in resource-limited settings.